Wikileaks news in the networked era - Beckett, Charlie; Ball, James (Polity Press, 2012)
WikiLeaks is the most challenging journalistic phenomenon to have emerged in the digital era. It has provoked anger and enthusiasm in equal measure, from across the political and journalistic spectrum. WikiLeaks poses a series of questions to the status quo in politics, journalism and to the ways we understand political communication. It has compromised the foreign policy operations of the most powerful state in the world, broken stories comparable to great historic scoops like the Pentagon Papers, and caused the mighty international news organizations to collaborate with this tiny editorial outfit. Yet it may also be on the verge of extinction. This is the first book to examine WikiLeaks fully and critically and its place in the contemporary news environment. The authors combine inside knowledge with the latest media research and analysis to argue that the significance of Wikileaks is that it is part of the shift in the nature of news to a network system that is contestable and unstable. Welcome to Wiki World and a new age of uncertainty.